ELECTORAL PROCESS. NOTION AND COMPOSING FACTORS - Поліщук, І.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The notion and composing factors of the political (electoral) process and also methodological aspects of the study of this enormous category of the political science are considered. Besides, here the democratization is defined as a leading tendency of the world and Ukrainian political process, the political and cultural factor is defined as one of the crucial tendencies in the electoral process.